2004
DOI: 10.1002/14651858.cd000201.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic ergometrine-oxytocin versus oxytocin for the third stage of labour

Abstract: Prophylactic ergometrine-oxytocin versus oxytocin for the third stage of labour (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
103
1
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(115 citation statements)
references
References 26 publications
4
103
1
7
Order By: Relevance
“…The results of our study were comparable with that of the other studies. Mcdonald and Abbott (2007-cochrane review) [10] compared effects of oxytocin with ergometrine-oxytocin in reducing risk of PPH (i.e. blood loss of 500 ml) and found that ergometrine-oxytocin was associated with small reduction in the risk of PPH (odds ratio = 0.82) but more of nausea, vomiting and hypertension.…”
Section: Resultsmentioning
confidence: 99%
“…The results of our study were comparable with that of the other studies. Mcdonald and Abbott (2007-cochrane review) [10] compared effects of oxytocin with ergometrine-oxytocin in reducing risk of PPH (i.e. blood loss of 500 ml) and found that ergometrine-oxytocin was associated with small reduction in the risk of PPH (odds ratio = 0.82) but more of nausea, vomiting and hypertension.…”
Section: Resultsmentioning
confidence: 99%
“…Administration of Oxytocin has been found to be associated with lesser blood loss in the third stage than expectant management. 12,13 But oxytocin need storage at low temperatures and a skilled person to administer the drug by intramuscular (IM) or intravenous (IV) route, which are not feasible in rural areas of resource poor countries like India.…”
Section: Introductionmentioning
confidence: 99%
“…In McDonald [6] study, it was observed that delayed cord clamping may help prevent iron-deficiency anemia during the first year of life [6]. On the other hand, iron deficiency anemia affect millions of children worldwide and in Saudi Arabia more than 350\100000 of infants are anemic before 6 months of age [7].…”
Section: Introductionmentioning
confidence: 99%